PTU-031 Duodenal Biopsy Specimen Collection And Diagnosis Of Coeliac Disease. (9th June 2014) - Morrow, J; Rafferty, G; Loughrey, M
Abstract : Introduction: Coeliac disease is an immune-medicated, gluten sensitive enteropathy affecting 1% of the UK population. 1 Early diagnosis is important due to the potential long-term complications. Histological analysis along with serum biomarkers are used in diagnosis. 1 British Society of Gastroenterology (BSG) guidelines recommend a minimum of 4 duodenal biopsies in order to maximise detection rates. 2, 3 Objectives: To determine the current practice relating to the number of duodenal biopsy specimens taken at endoscopy in Belfast HSCT compared to national guidelines, and to assess the correlation between serology results and subsequent diagnosis of coeliac disease. Methods: Retrospective review of the first 500 duodenal biopsy histology reports processed by Belfast Trust pathology laboratory in 2012. Positive/equivocal histological features based on criteria in BSG guidelines. 2 Serology results were checked via the Link Labs© system on all patients with pathology submitted. Results: 481 duodenal histology records were included in the study with 19 excluded. 225 specimens (46.7%) had less than the 4 recommended individual biopsy fragments. 26 patients were diagnosed with Coeliac disease based on histological findings, and a further 30 had 'equivocal' results. Patients with positive or equivocal coeliac histology had a higher percentage of 4 or more biopsies as compared to the whole group (80.7% and 77.3% respectively vs 53.3%). Overall 96% with histological evidence of coeliac disease also had positive serology (n = 23). For those with 'equivocal' histology, serology was positive in 55% and negative in 45%. 2% of patients with negative histology had strongly positive serology. Conclusion: The number of duodenal biopsy specimens taken at endoscopy is below recommended guidelines in 46.7% of cases. There is a higher number of biopsy specimens taken in those with subsequently positive or equivocal histological features. 96% of cases where histology was diagnostic also demonstrated positive serology. 2% of patients with subsequently negative histology had strongly positive serology prior to endoscopy, and in these cases almost all had 4 or more individual pathology specimens. This suggests that where strong clinical suspicion and positive biochemistry indicate a higher probability of coeliac disease, the endoscopist is inclined to take more biopsy specimens. References: Richey R, et al . Recognition and assessment of coeliac disease in children and adults: summary of NICE guidance. BMJ 2009 May 27;338:b1684 Ciclitira PJ, et al . The Management of Adults with Coeliac Disease . BSG Guidelines Rubio-Tapia A, et al . ACG clinical guidelines: diagnosis and management of celiac disease. Am J Gastroenterol 2013;108:656–676 Disclosure of Interest: None Declared.